The Relationship Between the Electrical Properties of Thick Film Resistors and the Thermal Expansion Coefficient of the Substrates - Toshio Inokuma; Yoshiaki Taketa; Miyoshi Haradome (Active and Passive Electronic Components)
The temperature characteristics of RuO2-based thick film resistors on various substratcs having different thermal expansion coefficient have been investigated.